2009
DOI: 10.1016/j.trstmh.2008.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Skin disorders and disease profile of poverty: analysis of medical records in Tigray, northern Ethiopia, 2005–2007

Abstract: Skin disease is among the most frequent causes of morbidity in Ethiopia, showing high prevalence in the general population and being the sixth most frequent cause of outpatient visits nationwide to health facilities. This study was aimed at describing skin disease patterns in Tigray region, northern Ethiopia through a retrospective analysis of 30618 outpatient and 1103 inpatient medical records from the Italian Dermatological Centre in Mekelle, the regional capital of Tigray, during the period 2005-2007. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 15 publications
2
47
0
2
Order By: Relevance
“…The finding that 59% of all the cases were tinea capitis, predominantly found among boys (93%), may increase the ratio as it did in other studies. 29,36,46 Kao 50 acknowledged this finding since he found a 5:1 male:female ratio for Microsporum audouinii-related tinea capitis. Hausa beliefs prescribe that a married woman must obtain the permission of the husband before leaving the house, and many Hausa fathers are reluctant to allow their daughters to make unescorted journeys for treatment, particularly if they consider the symptoms nonthreatening and treatable with homemade herbal treatment.…”
mentioning
confidence: 98%
“…The finding that 59% of all the cases were tinea capitis, predominantly found among boys (93%), may increase the ratio as it did in other studies. 29,36,46 Kao 50 acknowledged this finding since he found a 5:1 male:female ratio for Microsporum audouinii-related tinea capitis. Hausa beliefs prescribe that a married woman must obtain the permission of the husband before leaving the house, and many Hausa fathers are reluctant to allow their daughters to make unescorted journeys for treatment, particularly if they consider the symptoms nonthreatening and treatable with homemade herbal treatment.…”
mentioning
confidence: 98%
“…Few reports show the true extent of cutaneous diseases in Ethiopia, but according to some studies, 4 up to 80% of people have 1 or more skin diseases. In their study examining skin disease patterns in the Tigray region of northern Ethiopia, Accorsi et al 5 found that skin diseases represented the sixth most frequent cause of outpatient visits to health care facilities nationwide. Many elements influence the pattern and burden of skin diseases in resource-poor settings, including poverty, environmental, and climatic factors.…”
mentioning
confidence: 99%
“…This is particularly true in hot, humid tropical areas with overcrowding and lack of hygiene, where infections and infestations account for a significant proportion of cutaneous diseases. Accorsi et al 5 found that scabies infections were the leading cause of inpatient admissions in a northern Ethiopian hospital, where they accounted for 19.3% of total hospital admissions due to a skin disorder. At the Black Lion Teaching Hospital in urban Addis Ababa, Shibeshi 6 found that cutaneous infections were the second leading cause of disease among patients presenting with skin complaints after allergic skin diseases.…”
mentioning
confidence: 99%
“…3 In our area, we observed that some genetic diseases are relatively well represented, such as XP, ichthyoses, NF1, and tuberous sclerosis (TS), but this has not been documented yet. IDC is the only referral and training center for skin diseases, diagnosis, and care in the region.…”
Section: Introductionmentioning
confidence: 94%